A Holistic Conceptual Model of Hamka's Contemporary Islamic Educational Thought - Defriyanto Defriyanto; Oki Dermawan; Satria Adi Pradana; Khadijah Khadijah (Muaddib: Journal of Islamic Teaching and Learning, 2026)
This study presents an integrative–critical narrative literature review of Hamka’s educational thought. It maps dominant elements across the literature, clarifies relationships among conceptual components, and identifies areas that remain insufficiently connected. Using an integrative critical narrative review approach, the study analyzes 14 selected articles (2020–2025) that discuss Hamka’s educational ideas from multiple thematic angles. The findings show that scholarship most consistently foregrounds akhlaq/character/ethics as the central educational aim, supported by foundational elements tawhid/creed (aqidah) and tasawuf that orient values and cultivate the inner life. Moreover, the literature outlines Islamic educational processes through the frameworks of ta’lim–tarbiyah–ta’dib and knowledge–practice–ethics, while extending the discussion through educational values derived from Tafsir Al-Azhar and socio-cultural dimensions such as nationalism and the integration of Nusantara culture. Despite its thematic breadth, however, the literature remains largely fragmented and has not yet produced a unified framework linking value foundations, educational processes, moral aims, and contextual grounding. In sum, this review offers a holistic conceptual map that systematizes relationships among the dimensions of Hamka’s educational thought and highlights the need for further research that is more operational and context-sensitive.